1978
DOI: 10.1111/j.1476-5381.1978.tb17290.x
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Putative 5‐hydroxytryptamine Antagonists on the Behaviour Produced by Administration of Tranylcypromine and L‐tryptophan or Tranylcypromine and L‐dopa to Rats

Abstract: 1 The putative 5-hydroxytryptamine (5-HT) receptor blocking drugs methysergide (10 mg/kg) and methergoline (5 mg/kg) were found to abolish some components of the hyperactivity syndrome, including head weaving and forepaw treading, which follow administration to rats of tranylcypromine (20 mg/kg) and L-tryptophan (100 mg/kg). Hyperactivity and hyper-reactivity were potentiated with a resultant increase in automated locomotor activity counts. In contrast (-)-propranolol (20 mg/kg) inhibited all features of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

1978
1978
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 147 publications
(48 citation statements)
references
References 20 publications
6
42
0
Order By: Relevance
“…While methysergide and methergoline effectively blocked the behavioural changes, cyproheptadine, cinanserin and the peripheral 5-HT antagonist, xylamidine tosylate, were without activity (Clineschmidt, McGuffin & Pflueger, 1977 (Deakin & Green, 1978). The differing anatomical basis for the behavioural components may explain the differential effects of various 5-HT antagonists.…”
Section: Dmt-induced Hyperactivity In Micementioning
confidence: 99%
See 2 more Smart Citations
“…While methysergide and methergoline effectively blocked the behavioural changes, cyproheptadine, cinanserin and the peripheral 5-HT antagonist, xylamidine tosylate, were without activity (Clineschmidt, McGuffin & Pflueger, 1977 (Deakin & Green, 1978). The differing anatomical basis for the behavioural components may explain the differential effects of various 5-HT antagonists.…”
Section: Dmt-induced Hyperactivity In Micementioning
confidence: 99%
“…The differing anatomical basis for the behavioural components may explain the differential effects of various 5-HT antagonists. Thus, Deakin & Green (1978) have proposed that the ability of methergoline and methysergide to block some components of the behavioural syndrome while enhancing hyperactivity may be because these drugs do not block supra-spinal 5-HT receptors. Indeed, electrophysiological experiments indicate that many 5-HT responses are unaffected by methergoline or methysergide (Haigler & Aghajanian, 1977).…”
Section: Dmt-induced Hyperactivity In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Deakin & Green (1978) also demonstrated the inhibition of part of the syndrome by the 5-HT antagonists methergoline and methysergide. In addition they found that propranolol, when given before tryptophan and tranylcypromine, blocked all components of the syndrome.…”
Section: + 14(3)mentioning
confidence: 99%
“…Deakin & Green (1978) made specific chemical lesions of the 5-HT neurones in the spinal cord, and administered a 5-HT receptor agonist when sufficient time had elapsed for supersensitivity of the receptors to develop. Because headweaving, forepaw treading and limb abduction were increased in these animals they concluded that these facets of the syndrome were spinal while hyperactivity and hyper-reactivity were central in origin.…”
Section: + 14(3)mentioning
confidence: 99%